Analisis EPS, PER, TVA dan PBV Terhadap Keputusan Stock Split: Studi pada Perusahaan Manufaktur yang Tercatat di BEI Tahun 2016-2020 - Bima Zikrillah Haq; Dicky Jhoansyah; Kokom Komariah (Ekuitas: Jurnal Pendidikan Ekonomi, 2022)
The goals of the study was to measure the level of influence of the variable earning per share, price to earnings ratio, trading volume activity and price to book value on stock split decisions. This type of research was quantitative where the methods used are descriptive and associative methods. Sampling used in this study is by means of purposive sampling using 6 criteria. The analytical technique used is logistic regression, descriptive statistics, Hosmer and Lemeshow's Goodnes of Fit test, multicollinearity test, coefficient of determination testing and partial hypothesis testing used (t test) and simultaneous hypothesis used the F test. This study bring about, according to the t-test result shows PBV has a significant positive effect on stock split decisions, while EPS, PER, TVA, does not have a significant negative effect on stock split decisions, according to the f-test result shows EPS, PER, TVA and PBV have a simultaneous and significant influence on decisions stock splits.